2019
DOI: 10.1038/s41419-018-1288-0
|View full text |Cite
|
Sign up to set email alerts
|

CBX8 exhibits oncogenic properties and serves as a prognostic factor in hepatocellular carcinoma

Abstract: Polycomb group family is a class of proteins that have important roles in both physiological and pathological processes, and its family member Chromobox homolog 8 (CBX8) regulates cell differentiation, aging, and cell cycle progression in numerous carcinomas; however, the effects and underlying mechanisms of CBX8 in hepatocellular carcinoma (HCC) are rarely reported. We found that CBX8 expression in clinical HCC specimens correlates inversely with patient survival. In HCC cells, we found that enforced overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Moreover, recent studies have shown that CBX8 was deregulated in several kinds of tumors including HCC. CBX8 was over-expressed in HCC tissues and correlated with poor prognosis of patients [14, 15]. Mechanistically, CBX8 activates bone morphogenetic protein 4 (BMP4) transcription by modulating H3K27me3 [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies have shown that CBX8 was deregulated in several kinds of tumors including HCC. CBX8 was over-expressed in HCC tissues and correlated with poor prognosis of patients [14, 15]. Mechanistically, CBX8 activates bone morphogenetic protein 4 (BMP4) transcription by modulating H3K27me3 [15].…”
Section: Discussionmentioning
confidence: 99%
“…CBX8 was over-expressed in HCC tissues and correlated with poor prognosis of patients [14, 15]. Mechanistically, CBX8 activates bone morphogenetic protein 4 (BMP4) transcription by modulating H3K27me3 [15]. In addition, CBX8 could efficiently activate AKT/β-catenin signaling via up-regulation of the transcription factor EGR1 and miR-365-3p [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of CBX8 has been reported in various human cancers [15, 16, 2022, 24]. Growing research has shown the cell proliferation promoting effects of CBX8 in different types of cancers [15, 18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang’s and Bo Tang’s reports are consistent with our results and have further confirmed the reliability of our results. However, the mechanisms of malignant HCC progression are different [18, 22]. We first found a new important binding partner for CBX8, and found that CBX8 regulates the proliferation of HCC cells through the regulation of cell cycle pathways.…”
Section: Discussionmentioning
confidence: 99%